The Impact of Realistic Mathematics Education-based Student Worksheet for Improving Students’ Mathematical Problem-Solving Skills - Tumangger, Wana Rukmana; Khalil, Ibrahim Alhussain; Prahmana, Rully Charitas Indra (IndoMath: Indonesia Mathematics Education, 2024)
Mathematical problem-solving ability is a critical skill required to meet the challenges of the 21st century, making it imperative for Indonesian students to master these skills. However, international assessments have consistently shown that Indonesian students' competencies, particularly in mathematical problem-solving, remain low. Research attributes this deficiency to the lack of connections between mathematical concepts and real-life applications, which are essential for enhancing problem-solving skills. On the other hand, Realistic Mathematics Education (RME) is a learning approach that emphasizes the integration of real-world contexts in learning activities and has been shown to improve these skills. Therefore, this study aims to develop a student worksheet based on the RME approach to enhance students' problem-solving abilities. The development process followed the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Various research and development instruments were employed, including validation by material and media experts, student assessments of the electronic worksheets, and pre-test and post-test evaluations. Data collection methods encompassed both non-test and test techniques. The results demonstrate that the developed student worksheets are valid, practical, and effective. The validity was confirmed by high average scores from material and media expert validators, categorizing the worksheets as valid. Practicality was supported by positive student assessments, placing the worksheets in the practical category. These findings indicate that the developed worksheets significantly enhance students' problem-solving abilities. This study provides empirical evidence supporting the effectiveness of the RME approach in improving mathematical problem-solving skills among Indonesian students. It also offers a theoretical and practical framework for advancing mathematics education in Indonesia, advocating for the adoption of learning approaches that better address the demands of the 21st century. Detailed analysis of the product's acceptability and impact will be discussed further in the paper.